Pelatihan Pemanfaatan Software Geogebra dalam Pembelajaran Matematika pada MGMP Matematika - Ahmat Wakit; Lilik Sulistyo; Khotibul Umam; Ariyanto Ariyanto; Decky Rochmanto (Jurnal Pengabdian KOLABORATIF, 2024)
The Mathematics Subject Teacher Meeting (MGMP) at KKMA 02 Jepara is routinely held at least 3 times in a semester, namely at the beginning before learning begins, in the middle, and at the end of the semester. The routine activities carried out are discussing textbooks and worksheets, setting up learning traps, and preparing for the preparation of Mid-Semester Examination questions and Final Semester Examination questions. However, in the last few semesters, the Mathematics MGMP is rarely held, even in this semester there is only 1 meeting and there is no more meeting agenda. This is due to several factors such as the level of saturation because the activities carried out are the same, never innovative activities that are in nature to improve the abilities and skills of teachers such as training, this encourages community service programs to be held with the theme "Utilization of Geogebra software in learning mathematics". This activity is a training for teachers who are members of the Mathematics MGMP regarding the importance of Geogebra software in learning mathematics. The method used is lectures and discussions from presenters from UNISNU Jepara and continued with simulations. The results of this activity are increased teacher knowledge and skills in designing learning media and implementing Geogebra software-based mathematics learning. It is hoped that by increasing teacher skills in developing innovative learning media, the learning atmosphere in the classroom will be enjoyable and student interest and motivation in learning will increase.